ANOMALIES IN SOME FRESHWATER FISHES OF JAMMU (J AND K) - NISHA BHAGAT,; RAVINDER KUMAR,; RAJINDER SINGH, (The Bioscan, 2013)
In the present study six abnormal specimens of three different species of fish were noticed in a collection made from Ranjit Sagar reservoir built on river Ravi at Basholi (J and K) which included 4 deformed specimen of Cirrihinus mrigala, 1 aberrant specimen of Catla catla and 1 abnormal specimen of Labeo rohita. The deformities in these fish were studied through radiographic examinations. During the study it was discovered that all these deformities in the collected fish specimens are probably due to developmental error.